Overtraining and the BCAA hypothesis - Gastmann, U.; Lehmann, M. (Medicine & Science in Sports & Exercise, 1998)
The purpose of this review was to give an answer to the question whether there are convincing data to support the hypothesis of an amino acid imbalance as one possible mechanism to explain overtraining syndrome. Animal studies point to an enhanced synthesis of the neurotransmitter 5-hydroxytryptamine through an amino acid imbalance at the blood-brain barrier with a preferable tryptophan uptake into the brain, resulting in premature fatigue. Human studies, however, show contradictory results, mainly because of nonstandardized methodology, so that a final conclusion cannot be made at present. BCAA supplementation in addition to standard carbohydrate ingestion during sustained exercise seems to be of no eminent advantage to delay fatigue. The overall results concerning the BCAA hypothesis to explain overtraining are inconclusive and require more controlled experimental research.